Use of Ionic Liquids-like Surfactants for the Generation of Unilamellar Vesicles with Potential Applications in Biomedicine - Lépori, Cristian Marcelo Oscar (2019)
The goal of this work is to understand the influence of the counterion nature on the organized systems formed by 1,4-bis-2-ethylhexylsulfosuccinate surfactants in aqueous solutions and how these aggregates will influence the deoxyribonucleic acid (DNA)-surfactant interactions. With this in mind, two ionic liquid-like surfactants were investigated: 1-butyl-3-methylimidazolium 1,4-bis-2-ethylhexylsulfosuccinate (bmim-AOT) and 1-hexyl-3-methylimidazolium 1,4-bis-2-ethylhexylsulfosuccinate (hmim-AOT). Measurements of dynamic light scattering, ζ-potential, transmission electron microscopy, and fluorescence and UV-visible spectroscopy were performed to study the characteristics of the vesicles formed by bmim-AOT and hmim-AOT. Regarding the determination of the interaction of the surfactants with DNA, circular dichroism was used. The results obtained showed that bmim-AOT and hmim-AOT ionic liquid-like surfactants spontaneously form unilamellar vesicles in water at very low surfactant concentrations. The characteristics of these aggregates are dependent on the length of the tail of the counterions. The length of the hydrophobic chains of the counterions also influences the DNA-surfactant interactions through hydrophobic effects.